KUALITAS PELAYANAN TERHADAP KEPUASAN PUBLIK DALAM PEMBUATAN KTP DAN KK PADA DINAS KEPENDUDUKAN DAN CATATAN SIPIL KABUPATEN PIDIE - Rozaili Rozaili (Jurnal Sosial Humaniora Sigli, 2020)
Location of research "Quality of Service to Public Satisfaction in Making ID Card and Family Card at the Department of Population and Civil Registry of Pidie Regency". Which becomes one of the factors in this context are: 1. How is the quality of service to Public Satisfaction in the Making of KTP and KK at the Department of Population and Civil Registration of Pidie Regency, 2. The factors that become obstacles in providing services to the Public in making ID cards and KK at the Department of Population and Civil Registry of Pidie Regency. The method in this research is qualitative method that is written in the form of descriptive, while this research is research conducted at Department of Population and Civil Registry of Pidie Regency. While the object of research is an employee or government apparatus that provides services to the community in the making of KTP and KK, while the subject of research is the quality of service to the satisfaction of the community in making KTP and KK at the Department of Population and Civil Registry of Pidie District. The sampling technique in this research is using census technique that is all sample population, whereas because many writer take 20 sample people, and that become information in support of the data. KK, and Operator. The results of this study Quality of service to students in the making of ID card and KK at the Department of Population and Civil Registry of Pidie District Taking influence from the level of reliability, the level of responsiveness of employees, direct evidence, the ability of employees, government level, community level, communication level, the quality of service is good, from the level of public satisfaction (community) is the level of fulfillment of needs, achievements, and level of service provided by the Department of Population and Civil Registry of Pidie Regency is satisfied. Factors in providing services to the community who require KTP or KK at the Department of Population and Civil Registration Pidie District is a facility used, no blank ID card for this that comes from Jakarta, human resources are less competent, so many employees who contract employees , building facilities that do not have standards.